Analisis Perdagangan Internasional Terhadap Siklus Bisnis di ASEAN-5 Periode 1999-2014 - Atika Dinan; Haryo Kuncoro W.; Dicky Iranto (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2017)
This research is aimed to analyze the effects of International Trade to Business Cycle in ASEAN-5. The data used in this research are the panel data in period of 1999 – 2014 and in five country in ASEAN (Indonesia, Malaysia, Philippines, and Thailand). The The technique of data analysis in this research is Bayesian Vector Autoregressive (BVAR). Based on BVAR, the output has indicated the Openness to Trade and dummy Crisis are positively and significantly affected business cycles in ASEAN-5, and Intra Industry Trade is not affected to business cycles in ASEAN-5.